Penilaian Status Kesehatan Hutan Mangrove Di Desa Margasari Kecamatan Labuhan Maringgai Kabupaten Lampung Timur - Irlan Rahmat Maulana; Rahmat Safe'i; Indra Gumay Febryano (ULIN: Jurnal Hutan Tropis, 2021)
Mangrove forest ecosystems can be interpreted as a unique and distinctive form of ecosystem, so that it is able to provide many benefits, ranging from socio-economic or ecological terms to the surrounding ecosystem. Mangrove forest in Margasari Village is a mangrove forest ecosystem that has physical, economic and ecological potential that needs to be maintained through sustainable forest management. One of the ways to manage mangroves is by monitoring forest health. Forest health monitoring that is applied periodically within a forest type can achieve sustainable forest management achievements so as to support better forest quality and quantity and can be a reference in making the right decisions in mangrove forest management so that the results obtained can be optimal. This study aims to obtain the value of the health status of mangrove forests in East Lampung Regency in order to ensure the sustainability of the forest. The study was conducted using themethod Forest Health Monitoring (FHM). The results of forest health monitoring showed that there were 4 plot clusters with the final value of forest health status in the medium category plot 1 (5.63), cluster plot 2 (3.51) poor category, cluster plot 3 (4.92) poor category, and cluster plot 4 (7.57) in good category. Thus the results of forest health monitoring obtained in the mangrove forest of Margasari Village with an average final value of forest health status of 5.41 which is included in the medium category.